FILM DOKUMENTER SEBAGAI MEDIA PELESTARI TRADISI - Utami, Citra Dewi (Acintya, 2010)
the concern of tradition which is often said ancient becomes an idea of various arts. Tradition that is oftenly considered to be given things, one of them is penanggalan Jawa (Javanese calender), is sometimes ignored if is observed tradition of penanggalan jawa is still very closed to the society's social lives. Some daily activities are unconsciously planned based on the Javanese calender. Traditional is many times executed ritually. Sometimes people forget to inherit its phylosophy and use. Documentary film is one of audio visual media genres used to mediate the tradition preservation ad return which is essentially becomes a great heritage. Documentary film shows the importance of critizising the myth of various tradition.Keyword : documentary film, medition, tradition